2021
DOI: 10.1111/dom.14395
|View full text |Cite
|
Sign up to set email alerts
|

Longevity of the novel ConvaTec infusion set with Lantern technology

Abstract: Current insulin infusion sets are approved for only 2-3 days. The novel ConvaTec infusion set with Lantern technology is designed to extend infusion set wear time.The goal of this pilot study was to evaluate the duration of wear for this set. This was a pilot safety study in adults with type 1 diabetes using tethered insulin pumps. Participants inserted the set and wore it for 10 days or until failure. Among 24 participants, two were excluded. Forty-five per cent of the sets lasted 10 days. Median wear time wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 13 publications
1
34
0
Order By: Relevance
“…In conjunction with the fall in TIR, there was a reciprocal increase in time in hyperglycaemia suggesting a deterioration in glucose control when the set is worn beyond 72 h. In keeping with the aforementioned, TDD of insulin also increased with time. The increase in glucose levels with duration of IIS wear reflect the observations described in reports of other extended‐wear infusion set studies 11,12 …”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In conjunction with the fall in TIR, there was a reciprocal increase in time in hyperglycaemia suggesting a deterioration in glucose control when the set is worn beyond 72 h. In keeping with the aforementioned, TDD of insulin also increased with time. The increase in glucose levels with duration of IIS wear reflect the observations described in reports of other extended‐wear infusion set studies 11,12 …”
Section: Discussionsupporting
confidence: 82%
“…Other people report a worsening of glycaemic control over time, prompting them to change their IIS before the recommended 3‐day period 6,8,10 . Recently published data formally evaluating improved extended‐wear IISs have shown up to 7 days of wear time with reduced failures and increased patient satisfaction although some have reported an increase in average glucose per day of infusion set wear 11–15 . We suggest that there is room and a need for improvement in current IIS technology to increase the reliability of insulin delivery, reduce patient burden and minimize waste.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Preliminary research by ConvaTec, Medtronic, and Capillary Biomedical, among others, is showing the potential for infusion sets to function for 7–10 days. 120 The ConvaTec study published by Lal demonstrated a median wear time of 9.1 days. Such progress has the potential to limit set changes to a once-a-week occurrence, further reducing the burden of pump and AID system use.…”
Section: Expert Opinion On Potential Solutionsmentioning
confidence: 99%